The Role of Socio-Economic Factors in Enhancing Income and Resilience of Smallholder Farmers under Climate Change - Yadi Heryadi; Oktovianus; Risyart Alberth Far Far (CV. HEI PUBLISHING INDONESIA, 2026)
Climate change poses a significant economic threat to smallholder farmers, highlighting the importance of analyzing socio-economic factors that support resilience. This study investigates the determinants of agricultural income and household endurance amidst climatic anomalies by utilizing national-scale secondary data from the Indonesian Bureau of Statistics (BPS) and BMKG. Employing a dual econometric approach, Multiple Linear Regression (OLS) was used to identify income drivers, while Logistic Regression evaluated the probability of resilience. The findings indicate that human capital, specifically education and access to weather information, significantly enhances income efficiency, whereas climate anomalies persistently suppress productivity. Crucially, income diversification and participation in the Rice Crop Insurance (AUTP) scheme emerged as the strongest predictors of resilience, increasing recovery probabilities by factors of 3.12 and 2.45, respectively. This research concludes that fostering agricultural fortitude requires a strategic shift from traditional input subsidies toward comprehensive socio-economic empowerment and risk transfer mechanisms. These insights provide a critical framework for evidence-based policy interventions aimed at securing sustainable livelihoods for small-scale producers.